Phylogenetic analysis of human group C rotavirus in hospitalized children with gastroenteritis in Belém, Brazil. Issue 4 (28th September 2015) - Lobo, Patrícia dos Santos; de Fátima dos Santos Guerra, Sylvia; Siqueira, Jones Anderson Monteiro; Soares, Luana da Silva; Gabbay, Yvone Benchimol; Linhares, Alexandre C.; Mascarenhas, Joana D'Arc Pereira
Abstract : Group C rotavirus (RVC) is potentially an important pathogen associated with acute gastroenteritis (AG), especially in outbreaks. This study aims to detect and molecularly characterize RVC in hospitalized children with AG in Belém, Brazil. From May 2008 to April 2011, 279 stools were subjected to reverse‐transcription polymerase chain reaction targeting VP7, VP6, VP4, and NSP4 genes. RVC positivity rate was 2.1% (6/279) and phylogenetic analysis of positive samples yields genotype G4‐P[2]‐I2‐E2. No evidence of zoonotic transmission and VP7 gene demonstrated close relationship with Asian strains. RVC surveillance is worth to expand information on evolutionary and epidemiological features of this virus. J. Med. Virol. 88:728–733, 2016 . © 2015 Wiley Periodicals, Inc.